Visualization of argininosuccinate synthetase by in silico analysis: novel insights into citrullinemia type I disorders - Gu, Xia; Mo, Wenhui; Zhuang, Guiying; Shi, Congcong; Wei, Tao; Zhang, Jinze; Tu, Chiaowen; Cai, Yao; Liao, Biwen; Hao, Hu (Frontiers in Molecular Biosciences, 2024)
BackgroundCitrullinemia type I disorders (CTLN1) is a genetic metabolic disease caused by argininosuccinate synthetase (ASS1) gene mutation. To date, the human genome mutation database has documented over 100 variants of the ASS1 gene. This study reported a novel deletion-insertion variant of ASS1 gene and employed various prediction tools to determine its pathogenicity.MethodsWe reported a case of early-onset CTLN1. Whole exome sequencing was conducted to identify genetic mutations. We employed various structure prediction tools to generate accurate 3D models and utilized computational biology tools to elucidate the disparities between the wild-type and mutant proteins.ResultsThe patient was characterized by severe clinical manifestations, including poor responsiveness, lethargy, convulsions, and cardiac arrest. Notably, the patient exhibited significantly elevated blood ammonia levels (655 μmol/L; normal reference: 10–30 μmol/L) and increased citrulline concentrations (936 μmol/L; normal reference: 5–25 μmol/L). Whole exome sequencing revealed a in-frame deletion-insertion mutation c.1128_1134delinsG in the ASS1 gene of unknown significance, which has not been previously reported. Our finding indicated that the C- terminal helix domain of the mutant protein structure, which was an important structure for ASS1 protein to form protein tetramers, was indeed more unstable than that of the wild-type protein structure.ConclusionThrough conducting an in silico analysis on this unique in-frame deletion-insertion variant of ASS1, our aim was to enhance understanding regarding its structure-function relationship as well as unraveling the molecular mechanism underlying CTLN1.